Pengaruh Penggunaan Modifikasi Komponen pada Sistem Pengereman Motor Terhadap Behavior Pengendara Motor Berkapasitas Mesin 150-250 Cc - Oneil, Braga; Jeremiah, Morris; Triyanti, Vivi (Metris: Jurnal Sains dan Teknologi, 2025)
Vehicles are a means of mobility for society. However, the use of vehicles cannot be separated from the risk of accidents that may occur. In Indonesia, 133 million motorcycle accident cases were recorded in 2019. Accidents are influenced by many factors, one of which is brake failure. Brake failure itself is caused by overheating of the brake disc. Modifying the braking system is one of the measures taken to prevent overheating in the braking system. The application of braking system modifications on motorcycles may also influence rider behavior when on the road. In this study, an identification was carried out regarding the use of modifications to braking system components and their impact on motorcycle rider behavior, observed from several aspects: speeding, lane filtering, and panic braking. The identification was conducted using a questionnaire containing questions on the braking components modified by riders and their riding behavior related to such modifications. Based on the analysis of the data obtained, it was found that there were no significant differences in rider behavior across the three aspects—speeding, lane filtering, and panic braking—between different types of motorcycle braking system modifications.